Patient-reported Aesthetic Satisfaction following Facial Skin Cancer Module Surgery Using the FACE-Q Skin Cancer. Issue 9 (September 2019) - Vaidya, Toral S.; Mori, Shoko; Khoshab, Nima; Dusza, Stephen W.; Bander, Thomas; Matros, Evan; Rossi, Anthony M.; Nehal, Kishwer S.; Lee, Erica H.
Abstract : Background: Over 5 million basal and squamous cell skin cancers are diagnosed each year. Seventy to 80% of these cancers occur in the head and neck region, for which surgical excision is the standard treatment. As patient satisfaction and quality of life are among the most important outcomes in plastic and reconstructive surgery, understanding patient perception of aesthetic postoperative outcome is critical. The objective of this study was to assess aesthetic satisfaction following facial skin cancer surgery using the FACE-Q Skin Cancer Module in the context of sociodemographic and clinical factors. Methods: This is a single-center, cross-sectional study in a tertiary care cancer setting of patients who underwent facial skin cancer surgery from March 1, 2016, to March 31, 2018. Patients completed the FACE-Q Skin Cancer Satisfaction with Facial Appearance and Appraisal of Scar scales postoperatively, between May 21, 2018, and October 1, 2018. Results: Patients completed the Satisfaction with Facial Appearance (n = 405) and Appraisal of Scar scales (n = 408) postoperatively (response rate 39%). Lower postoperative facial appearance and scar satisfaction scores were associated with female gender, younger age (<65 years), surgery location on the lip or nose, repair by flap or graft, and greater defect size. Linear regression models established that younger age, female gender, nose location, and flap repair were independently predictive of lower aesthetic satisfaction. Conclusions: Sociodemographic factors, central facial location, and repair type strongly contribute to aesthetic satisfaction following facial skin cancer surgery. This patient-reported data may guide counseling regarding postoperative aesthetic outcome and inform patient expectations.